Examining the underlying structure of after-class boredom experienced by English majors. (June 2022) - Pawlak, Mirosław; Kruk, Mariusz; Zawodniak, Joanna; Pasikowski, Sławomir
Abstract: Learning a second and/or a foreign language (L2) is accompanied by both positive and negative emotions which influence the quality, dynamics and efficiency of this process. One of the achievement emotions that has only recently been recognized by second language acquisition (SLA) researchers as an important individual difference (ID) factor is boredom. The study reported in this paper aimed to identify factors constituting the structure of after-class boredom, a negative emotion that learners experience in out-of-class situations, whether completing tasks and activities assigned by the teacher or such that they choose of their own accord. It was also intended to examine the extent to which the intensity of boredom is affected by general boredom proneness and attainment, and to develop and validate a domain-specific scale tapping into this negative experience in after-class contexts. The study involved 107 English majors in Poland who filled out the Boredom in Learning English Outside of School Questionnaire (BLEOS). Using the Boredom Proneness Scale (BPS) and end-of-the-year examination grades, participants were divided into more and less susceptible to boredom as well as into high- and low-achievers. Exploratory factor analysis allowed extraction of three factors underlying after-class boredom: (F1) unwillingness to learn English and inability to find (interesting) tasks, (F2) lack of creativity, focus and involvement and (F3) altered time perception, underused language abilities and monotony. Statistically significant differences were detected between more and less boredom-prone students for all three factors.